Penghilangan / Penurunan Kadar Turunan-Turunan Phenol Pada Air Limbah Dengan Menggunakan Enzim Peroksidase Dan Koagulan - Aida Soelaeman (Balai Besar Kimia dan Kemasan, 1997)
An enzymatic method for removal of phenols from industrial wastewater was investigated. Peroxidase from horseradish was demonstrated to remove phenol and aromatic amines from aqueous solutions and to decolorize from phenolic industrial ejjluents. Phenol and phenol derivatives contained in wastewater can be removed by using peroxidase and coagulant.